The role of twins in the study of caries and their prevalence in the world and Ukraine - Костенко, Євген Якович; Добровольська, Маріанна Костянтинівна; Білинський, Олександр Ярославович (Actual Dentistry, 2019)
Summary. The paper analyze the literature of the causes of multiple pregnancy, as well as analyze and calculate the prevalence of mono- and dizigotic twins in Europe, Ukraine and the Transcarpathian region. It is established that the main reasons for increasing the number of twins births may be the widespread use of auxiliary reproductive technologies, and defined the regions with the highest birthrates of twins in Ukraine and the Transcarpathian region. Key words: multiple pregnancy, monozygotic twins, dizygotic twins, prevalence of twins.